Ganti Rugi Akibat Penyalahgunaan Artificial Intelligence (Deepfake) pada Citra Orang Terkenal di Facebook Berdasarkan Pasal 1365 BW - Rambu Maharani; Sri Maharani M.T.V.M (Jurnal Hukum Lex Generalis, 2025)
The development of artificial intelligence technology, commonly referred to as Artificial Intelligence (AI), has given rise to various new phenomena, one of which is deepfake. Deepfake is an application used to falsify videos and images to make them appear realistic. It is often misused to create fake content, including the misuse of the image of public figures on social media platforms, such as Facebook. This misuse negatively impacts reputation, privacy rights, and material interests. The aim of this research is to analyze the forms of compensation that can be imposed on parties who have harmed victims as a legal sanction based on Article 1365 of the Indonesian Civil Code (Burgerlijk Wetboek/BW) concerning Unlawful Acts (Onrechtmatige Daad). This study uses a normative juridical method with a conceptual and statutory approach, supported by primary legal materials through relevant laws and secondary legal materials from literature. The results of the analysis show that using deepfake to damage someone’s reputation by spreading false information constitutes an Unlawful Act. Victims have the right to claim compensation, both material and immaterial, provided that the elements of the Unlawful Act can be proven. Furthermore, there is a need to strengthen regulations regarding the use of artificial intelligence (AI) and to provide legal protection for victims, especially public figures who are frequently targeted in cases of deepfake misuse on social media. It is also recommended that there be collaboration between the government, digital platforms, and stakeholders to prevent and address the spread of deepfake-generated content.